Effect Of Stocking Density On The Growth Performance And Survival Of Green Lobster Puerulus (Penulirus Homarus) - Rita Rostika; Lim Leong Seng; Rinaldo Nurfaizi; Bayu Priyambodo; Irfan Zidni (International Journal Labs, 2024)
This research aims to discover the growth rate and survival of puerulus green lobster (Panulirus homarus) kept in varied densities in controlled containers. This research was conducted from August 2022 through September 2022 for 60 days at Koperasi Samudera Bahari Utama, Girimukti Village, Pelabuhanratu, Sukabumi District, West Java. The method used in this research was Completely Randomized Design (CRD) with 5 treatments and 3 repetitions. These treatments were, A (density 10 lobsters/container), B (density 15 lobsters/container), C (density 20 lobsters/container), D (density 25 lobsters/container), and E (density 30 lobsters/container). The effect of each treatment was tested using the f-test in analysis of variance (ANOVA) at 5% test interval. If a significant difference was found, it would be followed by Duncan’s multiple range test. The parameters observed in this research were Survival Rate (SR), Feeding Efficiency (FE), Growth (GR) and water quality in the research media. From the research analysis, it was found that the highest parameters for Puerulus’s survival rate was in density A (10 lobsters) at 100%, for feeding efficiency (EPP) was in density A (10 lobsters) at the highest value of 5.07%, and for weight growth (WG), length growth (LG) during the research was in density A (10 lobsters) at a value of 2.4 gram. The oxygen content obtained from this research had a mean value of 6.2 mg/L. And the pH value was 7.66. The temperature was kept at 27-30°C range and the good salinity for lobster growth was at 25–28 ppt range